Did compulsory wear regulations increase personal flotation device (PFD) use by boaters in small power recreational vessels? A before-after observational study conducted in Victoria, Australia. Issue 1 (2nd June 2014) - Cassell, Erin; Newstead, Stuart
Abstract : Objective: To estimate the effect of the 2005 Victorian mandatory personal flotation device (PFD) wearing regulations on PFD use by occupants of small (hull length ≤4.8 m) power recreational vessels. Design: Before-after observational study investigating the probability of PFD use among occupants of small vessels before and after the regulations were introduced compared with the probability of use by their counterparts on large power vessels (hull length >4.8–12 m) who were not required to wear PFDs before or after the regulations were introduced in the low-risk conditions in which observations occurred. Methods: Statewide observation surveys of boaters were conducted in peak boating periods between January and March 2005 (prelegislation) and 2007 (postlegislation). Data collection included size of vessel, age and sex of boaters, life jacket use, boat type, activity of boaters, type of waterway and weather and water conditions. Logistic regression modelling tested whether there were statistically significant differences in the change in the relative odds of occupants wearing PFDs from the preintervention to the postintervention period in small compared with large power recreational vessels. Results: The probability of PFD use increased from 22% to 63% on small power vessels compared with 12% to 13% on large vessels. Regression analysis showed a high statistically significant increase in the odds of PFD use on small vessels relative to large vessels (OR 6.2, 95% CI 4.2 to 9.3, p<0.001). No statistically significant effect on use on large vessels was associated with the regulation (OR 1.27, 95% CI 0.94 to 1.70, p=0.15). Relative to large vessels, on small vessels the odds of PFD use increased significantly in both sexes, all age groups, all vessel types and activity groupings except for towed water sports where the increase was only marginally statistically significant. Conclusions: The legislative intervention was successful in increasing PFD wearing in small vessels. However, visible enforcement and tougher penalties are needed to optimise compliance.